IMPORTANCE OF GREEN FINANCING AND PROSPECTIVE DIRECTIONS IN IMPLEMENTING UZBEKISTAN'S SUSTAINABLE DEVELOPMENT STRATEGY I (Marketing Journal, 2025)
This article analyzes the current state and development prospects of green finance in the Republic of Uzbekistan as an essential financial mechanism for achieving sustainable development goals. The study evaluates the institutional, regulatory, and market factors influencing the formation of the green finance sector in a transition economy. The research focuses on financial instruments supporting environmentally oriented projects, including green bonds, loans, and investments. International experience is co mpared with Uzbekistanʼs ongoing initiatives, such as the introduction of a “green” taxonomy and measures to attract private investments in sustainable infrastructure. The study employs comparative analysis, systematization, generalization, and a contextua l approach adapted to the countryʼs sustainable development model. The findings justify the need to expand the regulatory framework, ensure project transparency, strengthen institutional cooperation, and improve access of small and medium -sized enterprises to financial resources for ecological projects.
Keywords: green economy; green finance; sustainable development; Uzbekistan; green bonds; transition economy; climate policy